A Socio Political Status of Minorities in Pakistan - Prof. Dr. Iram Khalid; Muhammad Rashid (Journal of Political Studies, 2019)
The groups of people based on religion, language or ethnicity living in a state but in lesser numbers are called minorities. The minority groups have been living in Pakistan amicably since independence and have been playing their active role in the development of society especially in education and health sectors. Despite being living in conducive environment as good and responsible citizens, the minority groups have been facing inequality, discrimination and victimization by both the state and society. These minorities have been marginalized in almost every segment of life including employment, education, and top of all-the religious freedom. The minorities, especially the Christians have some serious issues about their security and often mention that they have been targeted especially under Blasphemy Law in which they have been prosecuted in the name of religion. Most of these blasphemy cases have been found out to be the result of personal enmity and religious vendettas. The government needs to address these issues of minorities on emergency footings for an inclusive and moderate Pakistani society.